About the Urban Responsibility of Society - Kogan, Leonid (project baikal, 2013)
The article is devoted to the formation of urban responsibility of society and contains the demands of citizens’ responsibility based on regularities of urban processes. The level of urban responsibility in our country does not correspond to what is prescribed by the modern political situation and the pressure of world periphery. It is necessary to form the state ideology of European urban civilization that stands up to national and ethnic enclavity and commercialization of interests of administrations of urban communities. It is necessary to return the leading role in civilized development to the biggest urban communities of Europe and the world.
Keywords: urban processes; urbanization; policy; middleness